Immune System Evasion Mechanisms in Staphylococcus aureus: Current Understanding - Hesham A. Malak; Hussein H. Abulreesh; Sameer R. Organji; Khaled Elbanna; Mohammed R. Shaaban; Samreen; Iqbal Ahmad; Ashwag Shami; Wafa A. Alshehri; Ashjan Khalel; Hiyam H. Abureesh; Fatimah H. Asiri; et al. (Journal of Pure and Applied Microbiology, 2020)
Staphylococcus aureus is a major human pathogen that may cause a wide range of infections and is a frequent cause of soft tissue and bloodstream infections. It is a successful pathogen due to its collective virulence factors and its ability to evade the host immune systems. The review aims to highlight how S. aureus destroys and damage the host cells and explains how immune cells can respond to this pathogen. This review may also provide new insights that may be useful for developing new strategy for combating MRSA and its emerging clones such as community-associated methicillin-resistant S. aureus (CA-MRSA).